Precisely Tailoring Molecular Structure of Doxorubicin Prodrugs to Enable Stable Nanoassembly, Rapid Activation, and Potent Antitumor Effect - Chengcheng Feng; Yuting Wang; Jiaxu Xu; Yanzi Zheng; Wenhu Zhou; Yuequan Wang; Cong Luo (Pharmaceutics)
Background: Achieving a balance between stable drug loading/delivery and on-demand drug activation/release at the target sites remains a significant challenge for nanomedicines. Carrier-free prodrug nanoassemblies, which rely on the design of prodrug molecules, offer a promising strategy to optimize both drug delivery efficiency and controlled drug release profiles. Methods: A library of doxorubicin (DOX) prodrugs was created by linking DOX to fatty alcohols of varying chain lengths via a tumor-responsive disulfide bond. In vitro studies assessed the stability and drug release kinetics of the nanoassemblies. In vivo studies evaluated their drug delivery efficiency, tumor accumulation, and antitumor activity in mouse models. Results: In vitro results demonstrated that longer fatty alcohol chains improved the stability of the nanoassemblies but slowed down the disassembly and drug release process. DSSC16 NAs (hexadecanol-modified DOX prodrug) significantly prolonged blood circulation time and enhanced tumor accumulation, with AUC values 14.2-fold higher than DiR Sol. In 4T1 tumor-bearing mouse models, DSSC16 NAs exhibited notably stronger antitumor activity, resulting in a final mean tumor volume of 144.39 ± 36.77 mm3, significantly smaller than that of all other groups (p < 0.05 by ANOVA at a 95% confidence interval). Conclusions: These findings underscore the critical role of prodrug molecule design in the development of effective prodrug nanoassemblies. The balance between stability and drug release is pivotal for optimizing drug delivery and maximizing therapeutic efficacy.